Fostering Scientific Citizenship in an Uncertain World Selected Papers from the ESERA 2021 Conference - Carvalho, Graça S.; Afonso, Ana Sofia; Anastácio, Zélia (Contributions from Science Education Research, 2023)
XIII, 324 p. 1 illus.